Intercomparing different devices for the investigation of ice nucleating particles using Snomax® as test substance - Wex, Heike; Augustin-Bauditz, S.; Boose, Y.; Budke, C.; Curtius, J.; Diehl, K.; Dreyer, A.; Frank, F.; Hartmann, S.; Hiranuma, N.; Jantsch, E.; Kanji, Z. A.; et al. (Atmospheric chemistry and physics. Discussions, 2014)
Seven different instruments and measurement methods were used to examine - the immersion freezing of bacterial ice nuclei from - Snomax® (hereafter Snomax), a product containing ice - active protein complexes from non-viable Pseudomonas syringae bacteria. - The experimental conditions were kept as similar as possible for the - different measurements. Of the participating instruments, some examined - droplets which had been made from suspensions directly, and the others - examined droplets activated on previously generated Snomax particles, - with particle diameters of mostly a few hundred nanometers and up to a - few micrometers in some cases. Data were obtained in the temperature - range from -2 to -38 °C, and it was found that all ice active - protein complexes were already activated above -12 °C. Droplets with - different Snomax mass concentrations covering 10 orders of magnitude - were examined. Some instruments had very short ice nucleation times down - to below 1 s, while others had comparably slow cooling rates around 1 K - min-1. Displaying data from the different instruments in - terms of numbers of ice active protein complexes per dry mass of Snomax, - nm, showed that within their uncertainty the data agree well - with each other as well as to previously reported literature results. - Two parameterizations were taken from literature for a direct comparison - to our results, and these were a time dependent approach based on a - contact angle distribution Niedermeier et al. (2014) and a modification - of the parameterization presented in Hartmann et~al.~(2013) representing - a time independent approach. The agreement between these and the - measured data were good, i.e. they agreed within a temperature range of - 0.6 K or equivalently a range in nm of a factor of 2. From - the results presented herein, we propose that Snomax, at least when - carefully shared and prepared, is a suitable material to test and - compare different instruments for their accuracy of measuring immersion - freezing.
Gesehen am 20.01.2021